School and academic knowledge: thinking and discussing environmental education for the construction of a critical society (Research, Society and Development, 2023)
The present work aims to see the multiple understandings about the discussions about the environment and about the development logics that are being explored more and more every day. Seeking to understand the different perspectives and approaches, inside and outside the walls that guard the academic community of the State University of Paraíba. Methodologically, its structuring relied both on quantitative aspects, while data were collected through questionnaires on Google Forms, and on qualitative aspects, through the use of a second research profile, of an exploratory nature, through from diverse sources, such as e-books, doctoral theses and articles focused on the area. Therefore, throughout the research, we were able to observe the level of knowledge of academics and civil society as a whole about the proposed themes, as well as their level of complexity. collected data and their particularities, which express the limited point of view on knowledge of environmental education and the use of renewable energies, showing a lack of understanding or a very superficial understanding of the global importance of the theme, as well as the Homeric impact that both can cause in the lives of individuals, directly or indirectly, not to mention the awareness and preservation of the environment. It is concluded that environmental education should be more worked on in the early years so that people can reflect that it is everyone's duty to respect the limitations of natural resources.